Analisis Parenting Sibling Rivalry pada Remaja Kembar - Insani, Syaibatul; Movitaria, Mega Adyna (Institut Agama Islam Sumatera Barat Pariaman, 2022)
The purpose of this study was to explain the morphology of competing behavior of twins based on parental care that occurred in Nagari Sicincin. This study uses qualitative techniques, and data analysis techniques used are interviews and observation. The research subjects were 4 pairs of twins and 8 people. The effectiveness of the data using data triangulation techniques at the source. Data analysis was carried out interactively where parents treated their children. Resolving conflicts that occur in Gemini. There are two problems that are treated differently in the family. Other causes of sibling competition are product competition, clothing changes, and gift giving in social situations where not all subjects receive the same goods. The forms of sibling rivalry behavior that occur can be divided into three aspects, namely physical, psychological, and social. The results of this study indicate that the role of the family in terms of function can be in the form of socialization, education and parenting. It provides emotional and material support. In this case, parents teach children first.